Fichte’s Interpretation of Kant in §6 of the Second introduction to the Science of Knowledge - Mulone, Marco (Con-Textos Kantianos. International Journal of Philosophy, 2025)
In spite of Fichte’s explicit intention to bring transcendental philosophy to completion, Kant notoriously rejected the entire Science of Knowledge. Through an analysis of §6 of the Second Introduction, where Fichte directly engages with the philosopher from Königsberg, this article aims to assess the reasons behind Fichte’s claim and Kant’s rejection.